EFEKTIVITAS MEDIA PEMBELAJARAN MATERI PELUANG BAGI SISWA TUNANETRA KELAS 5 SEKOLAH DASAR - Maslahah, Sayidatul; Hantoro , Arif Dwi; Prasetyo, Imam Budi; Sukinah, Sukinah (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2022)
This study aims to determine the effectiveness of probability learning media for students with visual impairments. The type of research used is quasi-experimental with a quantitative approach and a One Group Pre Test - Post Test Design. The results of the total accumulation in the pre-test, the five participants had an average score of 18.6 with a percentage of 37.2%. Meanwhile, when they got treatment by using probability learning media for Student With Visual Impairment and the post-test is done, the results of the accumulated scores obtained from the five participants are on average 44 with a percentage of 88%. Thus, the average score of the five subjects has positive changes by 25.4 with a percentage of 50.8%. In addition, because the results obtained by T arithmetic are the same as T table, T arithmetic is in the position of the rejection area for Ho with a significance level of 0.01. Therefore, based on these calculations, it can be concluded that Ho is rejected and Ha is accepted. So, the conclusion is that there is strong significant effectiveness in the probability learning media for Student With Visual Impairment.